The Influence of Financial and Environmental Literature Social on Financial Behavior Students Of Faculty Of Economics And Makassar Unismuh Business - Resa Nur Rokhmah (Pustaka Digital Indonesia, 2021)
The purpose of this study was to analyze and test the Effect of Financial Literacy and Social Environment on Financial Behavior of Students of the Faculty of Economics and Business Unismuh Makassa r. The type of data used in this study is quantitative data obtained from questionnaires distributed to students of the Management Study Program, Muhammadiyah University of Makassar . The results showed that the data used multiple linear regression with the help of the Statistical Package For The Social Science (SPSS) version 24. The results showed that the financial literacy variable had a positive and significant effect on financial behavior and the social environment had a positive and significant effect on student financial behavior.